Investigating the Impact of Service Quality and Perceived Value on Repurchase Intention with the Mediating Role of Brand Preference - Fallah, Amir Reza; Nabavi Chashmi, Seyed Ali (Future of Work and Digital Management Journal, 2026)
The purpose of this study is to investigate the impact of service quality and perceived value on customers’ repurchase intention, with an emphasis on the mediating role of brand preference in the insurance industry. This research is applied in terms of objective, and descriptive-survey and correlational in terms of methodology. The statistical population consists of Asia Insurance customers in Mazandaran province. Based on Cochran’s formula, 196 individuals were selected using non-probability convenience sampling. The primary data collection tool was a standard questionnaire with a 5-point Likert scale, the validity and reliability of which were confirmed through confirmatory factor analysis (CFA), Cronbach’s alpha, and composite reliability. Data were analyzed using SPSS and PLS software through structural equation modeling (SEM). The findings indicate that service quality and perceived value have a positive and significant effect on brand preference and repurchase intention. Furthermore, brand preference, in addition to having a positive effect on repurchase intention, plays a significant mediating role in the relationship between service quality and perceived value with repurchase intention. The results suggest that in order to increase repurchase intention, service organizations should focus on strategies to strengthen brand preference in customers’ minds, in addition to improving quality and perceived value.